The Nexus of Natural Gas Consumption and Carbon Emission in Asia Pacific - Hasdi Aimon; Anggi Putri Kurniadi (An Overview on Business, Management and Economics Research Vol. 2, 2023)
This chapter aimed to determine the natural gas consumption and carbon emission in the middle income group of natural gas supplying countries in Asia Pacific, (China, Indonesia, Malaysia, Myanmar and Vietnam) during the period 2000-2021 by applying the simultaneous equation analysis. Natural gas is a fossil fuel energy source. Natural gas contains many different compounds. The largest component of natural gas is methane, a compound with one carbon atom and four hydrogen atoms (CH4). Natural gas also contains smaller amounts of natural gas liquids (NGLs, which are also hydrocarbon gas liquids), and nonhydrocarbon gases, such as carbon dioxide and water vapor. We use natural gas as a fuel and to make materials and chemicals. According to the findings of this study, carbon emissions raise the real exchange rate, population, and natural gas output while decreasing natural gas consumption. Furthermore, use of natural gas raises natural gas output, GDP per capita, and energy intensity. This report advises the government to produce clean and efficient alternative energy in response to natural gas demand for domestic and international markets. Furthermore, in order to establish a balanced situation between human activities and natural circumstances, the government must transition from a natural gas energy system to a clean energy system.